A3B type asymmetric metallo phthalocyanines bearing carboxylic acid and tert-butyl groups: Photophysical, photochemical and aggregation properties - Gorduk, Semih; Avciata, Oguzhan (ELSEVIER SCIENCE SA, 2024)
In this study, A3B type asymmetric magnesium(II), zinc(II) and indium(III)chloro phthalocyanine derivatives bearing carboxylic acid and tert-butyl groups were synthesized and their photochemical, photophysical and aggregation properties for photodynamic therapy (PDT) application were investigated. In the first part of the study; phthalonitriles, which are the starting materials, were synthesized and then different phthalocyanine compounds were obtained from the synthesized phthalonitriles in the second part. The synthesized compounds were characterized using different techniques. At the same time, the photophysical and photochemical properties of the synthesized compounds were also investigated. The calculated singlet oxygen quantum values in DMSO are 0.30 for MgPc, 0.72 for ZnPc, and 0.62 for InPc in and these values in DMF are 0.25 for MgPc, 0.68 for ZnPc, and 0.60 for InPc after photochemical studies. The obtained results proved that the contribution of the substituents increased the therapeutic efficacy. Finally, our results show that all Pc derivatives have displayed desirable singlet oxygen, photodegradation, fluorescence and aggregation properties for PDT studies.
Keywords: Phthalocyanine; Asymmetric; Photophysicochemical; A 3 B type; Carboxylic acid; PHOTODYNAMIC THERAPY; ZINC(II); SUBSTITUENTS; PHOTOSENSITIZERS; DERIVATIVES; BEHAVIOR; SOLVENT; CANCER; Chemistry